Evaluation of in-vehicle technologies to prevent unlicensed driving in Queensland and Victoria. (June 2019) - Demmel, Sébastien; Freeman, James; Larue, Grégoire S.; Rakotonirainy, Andry
Highlights: A BCR analysis of a biometric interlock to prevent unlicensed driving is conducted. Unlicensed driving costs 480 million per year in QLD and VIC. Fingerprints and vascular patterns-based interlocks are the best technologies. Deployment should be mandated to all banned drivers. Previous recommendations to target all young drivers are not substantiated. Abstract: Unlicensed driving is a serious problem in many Australian states, with unlicensed driving-related crashes (UDC) costing up to 304 million per year in Queensland, and 176 million in Victoria. In this paper, we present a Benefit-Cost Ratio (BCR) analysis of a set of Intelligent Transportation Systems technologies aimed at preventing unlicensed driving by verifying the driver's identity through biometric technology, as well as the validity of their licence. Utilised together, the technology would essentially take the form of a licence interlock. The goal of this program of research (from which this paper stems) was to provide preliminary recommendations as to which technology is the most beneficial and should be implemented as part of a government-led program increasing the functionalities of electronic driving licences (EDL). The corresponding BCR analysis revealed that fingerprints and finger vascular patterns recognition technologies were found to systematically have the best BCRs. In regard to the most effective manner to implement the technology, a corresponding investigation with five scenarios revealed that the greatest benefits would be achieved with: (a) a mandatory system for all banned drivers (e.g., suspensions & disqualifications), and (b) a mandatory system for banned drivers under the age of 21 only. Scenario (b) performs extremely well, with returns of up to 16 times the investment with a simple fingerprint-based interlock. Although often more modest, all systems were found to have BCRs above 1 in all of the implementation scenarios except one. This paper further outlines the findings in regard to addressing the significant problem of unlicensed driving via emerging technologies.